Pengaruh pH Larutan Antosianin Strawberry dalam Prototipe Dye Sensitized Solar Cell (DSSC): Mochamad Choirul Misbachudin, Ferdy S. Rondonuwu, Adita Sutresno - Mochamad Choirul Misbachudin, Mochamad Choirul Misbachudin; Ferdy S. Rondonuwu, Ferdy S. Rondonuwu; Adita Sutresno, Adita Sutresno (Jurnal Fisika dan Aplikasinya, 2025)
The prototype of Dye Sensitized Solar Cell (DSSC) has been fabricated using anthocyanin extract from fresh strawberry as the photosensitizer. This DSSC consist of a pair of ITO-coated glass substrate as the electrode and counter electrode. Permeable TiO2 nanocrystal layer was deposited as fotoanoda and anthocyanin dye sensitized at the electrode, while the counter electrode was deposited carbon layer. Both electrodes were arranged in sandwich structure, separated by redox electrolyte (I-/I3- ). Solar cell was soaked in anthocyanin dye with different pH: pH 3.0, pH 2.5, and pH 2.0. The results showed that the solar cell soaked with pH 2.0 has the highest output, where it is obtained 45 uA of the short-circuit current (Isc) and 321 mV of the open-circuit voltage (Voc ), and 20 uA/cm2 of current density (Jsc). While the energy conversion efficiency is 2.560x10-3 %.